Molecular Characterization and Gene Expression of Glutathione Peroxidase 1 in Tor tambroides Exposed to Temperature Stress. (June 2019) - Do, Thinh Dinh; Thi Mai, Nguyen; Duy Khoa, Tran Nguyen; Abol-Munafi, Ambok Bolong; Liew, Hon Jung; Kim, Chang-Bae; Wong, Li Lian
Temperature is an abiotic factor that affects various biological and physiological processes in fish. Temperature stress is known to increase the production of reactive oxygen species (ROS) that subsequently cause oxidative stress. Fish is known to evolve a system of antioxidant enzymes to reduce ROS toxicology. Glutathione peroxidase (GPx) family consists of key enzymes that protect fish from oxidative stress. In this study, full-length GPx1 cDNA (GenBank accession no. KY984468) of Tor tambroides was cloned and characterized by rapid amplification of cDNA ends (RACE). The 899-base-pair (bp) GPx1 cDNA includes a 576-bp open reading frame encoding for 191 amino acids, plus 28 bp of 5′-untranslated region (UTR) and 295 bp of 3′-UTR. Homology analysis revealed that GPx1 of T tambroides (Tor-GPx1) shared high similarity with GPx1 sequences of other fish species. The phylogenetic construction based on the amino acid sequence showed that Tor-GPx1 formed a clade with GPx1 sequences of various fish species. Real-time polymerase chain reaction (PCR) was performed to assess the levels of GPx1 gene expression in the liver and muscle of T tambroides under thermal stress. The results indicated that GPx1 gene expression was down-regulated under decreased temperature. However, there was no significant difference between GPx1 gene expression in fish exposed to high temperature and control. Our study provides the first data regarding GPx gene expression in T tambroides under thermal stress.